Post-Foreclosure Conveyance of Occupied Homes and Preferential Sales to Nonprofits: Rationales, Policies, and Underlying Conflicts. Issue 1 (2nd January 2017) - Bratt, Rachel G.
Abstract: This article explores the reasons why the conveyance of foreclosed homes with occupants makes sense, and why nonprofits should be given preferential treatment as purchasers, as well as the relevant policies and practices of the U.S. Department of Housing and Urban Development and the Federal Housing Administration (HUD/FHA) and the Federal Housing Finance Agency and the Government-Sponsored Enterprises (FHFA/GSEs). It also presents recommendations for revising current policies, and suggestions for further research. These issues also raise underlying questions about how the federal agencies view their public purpose roles and the implications for possible increased long-term public costs to shelter low-income households displaced because of foreclosure of their homes. Although HUD/FHA's guidelines allow for conveyance of foreclosed homes with occupants, the evidence—interviews with key stakeholders in Boston and data obtained from HUD through a Freedom of Information Act (FOIA) request—reveal that the guidelines are largely irrelevant in practice. Although there has been a change in an FHFA policy that could soften the GSEs' practice of no occupants at conveyance, it is not yet clear whether this will result in former owners and tenants being allowed to remain in their homes following foreclosure. Concerning preferential sales to nonprofits, whereas positive new policies have been issued by both the FHFA and HUD, the extent of implementation is not known. Finally, it appears that HUD/FHA and the FHFA/GSEs view foreclosed homes more as financial assets, whose value they seek to maximize, rather than as dwellings for financially strained households that, if evicted, may need additional housing subsidies and as part of a strategy to preemptively stabilize neighborhoods.